The Influence of Knowledge, Motivation, Leadership, and Workload toward Public Health Center Midwives’ Performance in Facilitative Supervision of MCH Program in Lumajang District - Isa Ma’rufi; Farida Wahyu Ningtyias; Mardiyanti Mardiyanti (Humanistic Network for Science and Technology (HNST), 2018)
Facilitative supervision by coordinator midwife of Public Health Center (PHC) to the midwife of village in Lumajang District carried out since 2009, but until now the implementation has not been effective. This can be seen from the secondary data Lumajang District Health Office 2016 are 56% of PHC reported results late facilitative supervision MCH program. Preliminary study shows the results of 70% of midwives in the villages do not get facilitative supervision by a midwife of PHC regularly; 60% of midwife of PHC did facilitative supervision visits to the midwife in accordance with the agreement stipulated period; and 60% expressed no real follow-up from the supervisors to the problems faced. This study was conducted to determine the variables that affect the implementation of facilitative supervision MCH program in Lumajang. The study design was an observational analytic. The sampling technique study determined through proportional cluster sampling. Based on the survey results revealed knowledge (r = 0.625), motivation (r = 0.658), perceptions of leadership (r = 0.711) had a strong relationship to the performance center midwife in the implementation and supervision facilitative MCH programs, while the workload (r = 0.585) had moderate level relationship to the dependent variable.Keywords: Supervision, Midwives, Performance